Understanding the molecular basis of a ubiquitin-dependent kinase and ubiquitin ligase at the interface of inflammation and cell death - Dietz, L (2023)
Inflammation and programmed cell death (PCD) are seemingly opposing yet intricately linked processes controlled through degradative and non-degradative ubiquitin chains. In this study, I report on two crucial components within apoptosis, a form of PCD, and inflammation. Firstly, the giant inhibitor of apoptosis (IAP), BRUCE, and how it mediates caspase inhibition and secondly how the TAK1-TAB complex undergoes activation by Lys63-linked chains.